Temple Volumization With Autologous Fat: A Systematic Review of the Literature - Friedmann, Daniel P; Hinchee-Rodriguez, Kathryn; Verma, Kritin K (Dermatologic surgery, 2025)
Facial aging leads to cosmetically unappealing temporal volume loss. To systematically review the literature regarding temporal volumization with autologous fat. PubMed, Scopus, Embase, and Cochrane databases were queried with relevant terms for all articles describing temporal volumization with autologous fat. Studies unrelated to temporal volumization, using synthetic fillers, without novel clinical/patient data, or unavailable in English were excluded, as were published abstracts of already included studies or with insufficient detail. Included article reference lists were also reviewed. Database query yielded 1,224 unique articles. After screening, evaluation for duplicates and inclusion/exclusion criteria, and reference review, 45 articles with 1,239 patients were included and analyzed. Significant improvements in subcutaneous fat thickness/augmentation and investigator-/subject-graded efficacy criteria were reported, with a mean volume retention rate of 42.11% ± 11.50% (32.6%-65.7%) at 12 months. Ecchymosis (43.68%, 114/261) was the most common posttreatment adverse event. No infections, nerve dysfunction, or fat necrosis were described. Two cases of cutaneous necrosis/scarring and 22 cases of embolic serious adverse events leading to ocular injury, neurologic impairment, and/or death were reviewed. Temporal volume loss can be effectively improved with autologous fat. Although predominantly a safe procedure, rare yet serious adverse events due to distal embolization have been reported.